2018
DOI: 10.1016/j.aap.2018.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Red-light running behavior of cyclists in Italy: An observational study

Abstract: Accident analysis and studies on traffic revealed that cyclists' violation of red-light regulation is a typical infringement committed by cyclists. Furthermore, an association between cyclists' crash involvement and red-light violations has been found across different countries. The literature on red-light running cyclists' behavior in relation to their characteristic is still scarce. The present study, adopted an eye-observational methodology to investigates differences in cyclists' crossing behavior at inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
17

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 30 publications
2
28
0
17
Order By: Relevance
“…More germane to this work, Prati et al adopted an eye-observational methodology to investigate differences in cyclists' crossing behavior at intersections, paying particular attention to demographic characteristics [25]. Results here, for example, showed that visual search strategies across different types of cyclists moderated the probability of running a red-light.…”
Section: Methods To Analyze Cyclists' Behavior At Intersectionsmentioning
confidence: 83%
“…More germane to this work, Prati et al adopted an eye-observational methodology to investigate differences in cyclists' crossing behavior at intersections, paying particular attention to demographic characteristics [25]. Results here, for example, showed that visual search strategies across different types of cyclists moderated the probability of running a red-light.…”
Section: Methods To Analyze Cyclists' Behavior At Intersectionsmentioning
confidence: 83%
“…Among all the aforementioned factors, the behavior of road users has been proven to be the most immediate determinant of crash involvement [26], with cyclists not being an exception [27]. It is estimated that 60% of the fatal crashes involving cyclists are incurred by their undesirable behaviors such as red-light running, distracted riding, and the occupation of motorized vehicle lanes, and a large proportion of cycling-related crashes involve more than one dangerous cycling behavior [25,28,29]. Martínez-Ruiz et al, [30] noticed that when carrying a passenger or cycling under the influence of alcohol or drugs, the risk of being involved in single-vehicle crashes and collisions with another vehicle was substantially increased.…”
Section: Factors Related To Crashes Involving Cyclistsmentioning
confidence: 99%
“…So far, most existing evidence has revolved around the red-light infringement behavior of cyclists. Specifically, investigations have been performed on the influence of demographics [11][12][13][14][15], psychological factors [11][12][13], and other risk behaviors (e.g., unhelmeted riding, carrying passengers, using a phone, and listening to music) [14,16,22,23] on cyclists' RLR behavior. However, due to the differences in weight, speed, and acceleration of e-bikes and regular bicycles, there are some discrepancies in the riders' psychology.…”
Section: E-bikers' Rlr Behaviormentioning
confidence: 99%
“…Some studies reported that the speed and weight of e-bikes were both higher than those of regular bicycles, thereby leading to more injuries and fatalities [9]. In addition, previous findings showed that traffic violating behaviors, especially red-light running (RLR) behavior at signalized intersections, partially contributed to e-bikers-related accidents and fatalities [10][11][12][13][14][15][16]. us, studies on e-bikers' RLR behavior are needed, especially for countries with high e-bike ownership and e-bike-involved accidents.…”
Section: Introductionmentioning
confidence: 99%